AB0148 Leucine-Rich Alpha-2 Glycoprotein is A Potential Disease Activity Marker under IL-6 Suppression in Autoimmune Arthritis. (10th June 2014) - Mishima, T.; Serada, S.; Fujimoto, M.; Hattori, K.; Ogata, A.; Nanki, T.; Takeuchi, T.; Naka, T.
Abstract : Background: C-reactive protein (CRP) is frequently used to evaluate inflammation in patients with rheumatoid arthritis (RA). However, CRP is normalized when IL-6 function is potently suppressed by anti-cytokine biologics such as tocilizumab. Therefore, novel biomarkers are required for accurate and sensitive assessment of the inflammation during anti-cytokine therapy. By proteomic screening of sera from patients with rheumatoid arthritis (RA), we previously identified serum leucine-rich alpha-2 glycoprotein (LRG) as a potential biomarker that reflects disease activity in RA better than CRP. Objectives: This study is aimed to investigate the clinical significance of LRG as a biomarker of RA disease activity during anti-IL-6 therapy. Methods: As a preclinical testing, cynomolgus monkeys with collagen induced arthritis (CIA) were treated with anti-IL-6 receptor antibody (anti-IL-6R mAb) and joint swelling and rigidity were scored for clinical assessment of arthritis throughout the experiment. At the time of sacrifice, blood samples were collected to be subjected to the measurement of LRG and CRP. RA patients treated with tocilizumab were enrolled and clinical disease activity index (CDAI) and serum levels of LRG and CRP were evaluated. Results: In CIA monkeys with anti-IL-6R mAb treatment, plasma LRG levels correlated better with disease activity than plasma CRP levels, presumably due to the fact that LRG levels were elevated in some animals with negative CRP in spite of high arthritis scores. Furthermore, among tocilizumab-treated patients for 6 months with normalized CRP levels (<0.2 mg/dL), serum LRG levels were significantly higher in patients with active RA (defined by CDAI>10) than those with RA with low disease activity (CDAI≤10). Conclusions: Our study indicates that LRG is a promising biomarker for monitoring disease activity in RA, even when CRP levels are reduced or normalized by anti-cytokine therapy. References: I Navarro-Millán et al. Systematic Review of Tocilizumab for Rheumatoid Arthritis: A New Biologic Agent Targeting the Interleukin-6 Receptor Clin Ther 2012; 34: 788-802 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2180